Students' question asking process: a model based on the perceptions of elementary school students and teachers - Dogan, Fatma; Yucel-Toy, Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The purpose of this study is to examine the perceptions of fourth-grade elementary school students and their teachers regarding students' asking-question in order to develop a model of students' asking-question process. A phenomenological research has been utilized and interviews were conducted with seven teachers and nine students from three public elementary schools in Istanbul, Turkey. The results showed that students generally ask questions when they are curious about the topic and want to learn the topic. Teachers pointed out situations encouraging students to ask such as creating a comfortable and active classroom environment, designing interesting activities fostering questioning, welcoming students' questions, and being a role model for asking good questions. There is also evidence that teachers' reactions such as being nervous or uncomfortable, ignoring them, not responding and classmates' reactions such as making fun of, humiliating, not listening to are considered as obstacles for students while asking questions. Moreover, it was concluded that students' questions have affirmative effects on both students and teachers. Finally, based on these results, a three-stage cycled model was developed; antecedents (internal and external causal factors), action-reaction (the act of asking questions, the reaction of teachers and classmates) and impact (impact on students and teachers).
Keywords: asking questions; student questions; elementary education; phenomenological research; PUPILS; Education & Educational Research